Analisis Kualitatif Perilaku Masyarakat Terhadap Pencegahan Penyakit Filariasis Di Desa Matang Pelawi - Masriana; Juliandi; Iman Muhammad (STIKes Payung Negeri Pekanbaru, 2019)
Filariasis is a chronic infectious disease, caused by filaria worms and transmitted by mosquitoes. Community behavior that lacks hygiene is thought to be the cause of transmission of filariasis. The purpose of this study is to qualitatively analyze community behavior towards the prevention of filariasis. This type of research is qualitative research. The research was conducted in Matang Pelawi Village, Peureulak Health Center. Research informants were 4 people. Qualitative data analysis with stages of data reduction, data display, and conclusion or verification. The results showed that the knowledge of the Matang Pelawi community about filariasis and its prevention, some already understood, while some other people did not understand about the causes, transmission, signs and symptoms, prevention and treatment. The attitude community about filariasis, some consider medical diseases because they can affect anyone and some consider non-medical diseases or because of mystical (black magic). Some people have a negative attitude by mocking, insulting and wanting that filariasis sufferers be exiled from their villages because it can bring bad luck to other residents. The actions community are partly understood about filariasis, by taking precautions such as maintaining the cleanliness of the living environment, sleeping using mosquito nets, and taking medicine in the Elephants Elimination Month (BELKAGA) in October each year. The conclusion of the study is that community behavior is related to knowledge, attitudes, and actions, some have been good because they have received counseling from health workers.